Platelet Count and Transfusion Requirements During Moderate or Severe Postpartum Haemorrhage. Issue 2 (June 2017) - Jones, R.M.; de Lloyd, L.; Kealaher, E.J.; Lilley, G.J.; Precious, E.; Burckett st Laurent, D.; Hamlyn, V.; Collis, R.E.; Collins, P.W.
Abstract : ( Anaesthesia . 2016;71:648–656) Postpartum hemorrhage is a leading cause of maternal morbidity and mortality worldwide. Depletion of coagulation factors and platelets can occur during obstetric hemorrhage. Reduction in coagulation factors and its management by replacement with fresh frozen plasma, cryoprecipitate, and fibrinogen concentrate have been addressed in earlier studies. However, there are few data addressing the need for platelet transfusion during postpartum hemorrhage. Current guidelines suggest transfusion may be indicated when the platelet count is <75×10 9 /L. This study evaluated data from a previous study investigating the effect of fibrinogen on postpartum hemorrhage progression to assess the association between baseline platelet count and the need for platelet transfusion during postpartum hemorrhage.